A phase 2 cooperative group adjuvant trial using a biomarker‐based decision algorithm in patients with stage I non‐small cell lung cancer (SWOG‐0720, NCT00792701). Issue 15 (18th April 2014) - Bepler, Gerold; Zinner, Ralph G.; Moon, James; Calhoun, Royce; Kernstine, Kemp; Williams, Charles C.; Mack, Philip C.; Oliveira, Vasco; Zheng, Zhong; Stella, Philip J.; Redman, Mary W.; Gandara, David R.
Abstract : BACKGROUND: This cooperative group adjuvant phase 2 trial in patients with completely resected stage I non‐small cell lung cancer with tumor diameters measuring ≥ 2 cm was designed to assess the feasibility and preliminary efficacy of assigning patients to therapy or observation using a molecularly based decision algorithm. METHODS: At least a lobectomy and sampling of recommended mediastinal lymph node stations, good Zubrod performance status, adequate organ function, and a formalin‐fixed and paraffin‐embedded tumor specimen were required. Excision repair cross‐complementing group 1 (ERCC1) and ribonucleotide reductase M1 (RRM1) were analyzed using immunofluorescence‐based in situ automated quantitative image analysis and categorized as high or low using prespecified cutoff values. Patients with high ERCC1 and RRM1 were assigned to observation and all others to 4 cycles of cisplatin and gemcitabine. Feasibility was defined as treatment assignment within 84 days from surgery in > 85% of patients. Secondary objectives were to estimate the 2‐year survival. RESULTS: Treatment assignment met the feasibility criteria in 88% of eligible patients (71 of 81 patients). The collective 2‐year disease‐free and overall survival rates were 80% and 96%, respectively. Protein levels for RRM1 fell within the previously established range, ERCC1 levels were slightly lower than expected, and they were significantly correlated (correlation coefficient, 0.4). The rates of assignment of patients to observation (22%) and chemotherapy (78%) were as expected. CONCLUSIONS: Gene expression analysis for treatment assignment is feasible. Survival results are encouraging and require future validation. Real‐time performance of quantitative in situ ERCC1 and RRM1 analysis requires further development. Cancer 2014;120:2343–2351 . © 2014 The Authors. Cancer published by Wiley Periodicals, Inc. on behalf of American Cancer Society . Abstract : Excision repair cross‐complementing group 1 (ERCC1) and ribonucleotide reductase M1 (RRM1) are promising predictive markers for the efficacy of platinum agents and gemcitabine. The current phase 2 trial was designed to assess the feasibility and preliminary efficacy of using molecular testing of surgically resected tumor specimens for therapeutic decision‐making in a cooperative group environment.